2014
DOI: 10.1123/jsm.2013-0146
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Contract of Volunteer Youth Sport Coaches

Abstract: This study examined the psychological contract of volunteer youth sport coaches to determine the content, variation, and influences to its development. Interviews were conducted with 22 volunteer coaches of team sports, representing different levels of play (recreational, competitive), coaching tenure (novice, experienced), and gender (female, male), who were sampled to account for the potential variation based on these demographic factors. The findings revealed that volunteer coaches possessed both transactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
2
31
0
1
Order By: Relevance
“…This study has extended our understanding of the relationship between volunteer recruitment practices and the development of volunteers' PC which had not been previously reported in the literature (Farmer & Fedor, 1999;Harman & Doherty, 2014;Hoye et al, 2008;Nichols, 2012). This study may provide organisations with the opportunity to identify and utilise formal recruitment practices that better support both the development of positive volunteer PCs as well as meeting the expectations of volunteers' PCs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This study has extended our understanding of the relationship between volunteer recruitment practices and the development of volunteers' PC which had not been previously reported in the literature (Farmer & Fedor, 1999;Harman & Doherty, 2014;Hoye et al, 2008;Nichols, 2012). This study may provide organisations with the opportunity to identify and utilise formal recruitment practices that better support both the development of positive volunteer PCs as well as meeting the expectations of volunteers' PCs.…”
Section: Discussionsupporting
confidence: 55%
“…In a similar vein, a PC represents the understandings held by volunteers regarding promises made between them and their respective NFP organisations (Rousseau & McLean Parks, 1993). Knowing the nature of these respective understandings is important for both volunteers and managers within NFP organisations because they both use their perception to interpret whether the relationship is good or not (Harman & Doherty, 2014). From the perspective of the NFP, it is likely that the simplest of promises made when a volunteer was recruited will be the only ones considered when evaluating the relationship (Nichols & Ojala, 2009).…”
Section: Psychological Contract Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…With its grounding in social exchange theory, PC, defined by Rousseau (1995) as the informal reciprocal agreement of a work environment from the individual's perspective, is a concept useful for explaining the relationship between an individual and an organization. Many scholars applied PC theory to exploring volunteers' motivation, performance, perceived support, satisfaction, and behavioral intention because it provides a valuable framework for examining the work environment and understanding volunteers' contributions (Accadia & Walker, 2009;Farmer & Fedor, 1997;Harman & Doherty, 2011;Starnes, 2007). Liao-Troth (2005) presented two interesting studies using a PC approach and found that agreeableness and emotional stability were related to the relational PC.…”
Section: Volunteers' Perceived Psychological Contractmentioning
confidence: 99%
“…The pivotal role of sport volunteers as social capital for the viability of the sport system has been acknowledged and studied by a plethora of academic re-searchers during the past decade (Bang & Ross, 2009;Harman & Doherty, 2014;Kim, Trail, Lim, & Kim, 2009;Peachey, Bruening, Lyras, Cohen, & Cunningham, 2015;Reeser, Berg, Rhea, & Willick, 2005;Strigas & Jackson, 2003). The nature of these studies varies, with some emphasis on event volunteerism (e.g., Kim et al, 2009), and others are executive or coaching volunteer roles (e.g., Harman & Doherty, 2014). Whatever the nature of the context, volunteers are an important element to various sporting endeavors because they provide sport managers with the ability to offer and sustain events, as well as expand the quantity, quality, and diversity of a sport organization's services (Strigas & Jackson, 2003).…”
Section: Theoretical Perspectives On Sport Volunteerismmentioning
confidence: 99%